1986
DOI: 10.2307/3676816
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Secondary Sexual Plumage Colour Characteristics of the Male Pied Flycatcher

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Gene flow from light coloured populations, sympatric with the collared flycatcher, has been suggested as a mechanism that could maintain colour polymorphism in allopatric populations ( Røskaft et al . 1986 ; Røskaft & Järvi 1992; Huhta & Siikamäki 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow from light coloured populations, sympatric with the collared flycatcher, has been suggested as a mechanism that could maintain colour polymorphism in allopatric populations ( Røskaft et al . 1986 ; Røskaft & Järvi 1992; Huhta & Siikamäki 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A typical passerine that shows a high level of fidelity to the breeding territory in successive breeding seasons is the Pied Flycatcher (Ficedula hypoleuca) (Lundberg and Alatalo 1992). Because of this, female and male local return rates have repeatedly been used in analyzing annual survival rates (Askenmo 1979, Røskaft et al 1986, Jä rvi et al 1987, Slagsvold and Lifjeld 1988, Alatalo and Lundberg 1989, Potti and Montalvo 1991a, Sanz 1997a, Siikamäki and Hovi 1997, Eeva and Lehikoinen 1998, Hemborg and Lundberg 1998, Hemborg 1999. In those studies, local return rate was often estimated as the proportion of marked individuals realized in one year that were recaptured in the next year.…”
mentioning
confidence: 99%
“…The distribution of light-coloured populations of Pied Flycatcher to a large extent coincides with the area of sympatry (Roskaft and Jirvi 1992). The females of the two flycatcher species are very similar, and it has been suggested that in sympatry the function of the female-like plumage colour of male Pied Flycatchers is to mimic the female Collared Flycatcher (Roskaft et al 1986, Kril et al 1988). This would help the subordinate species to establish territories in good quality habitats among the dominant competitor.…”
Section: Resultsmentioning
confidence: 95%
“…The local population is light-coloured (mean colour score: 6.2; Kril 1991) compared with Fennoscandian populations (3.2-3.9; Roskaft et al 1986). I presented a brown-coloured male (colour score 7) in a small (38 dm3) wire netting cage to unmated, male Pied Flycatchers, following the procedure of Saetre and Slagsvold (1992).…”
Section: Methodsmentioning
confidence: 99%